Penerapan Layanan Konseling Kelompok Untuk Meningkatkan Pengendalian Emosi - Achmadi Nugroho (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2023)
Group group services are the provision of assistance to individuals through group activities (Group Dynamics) which can enable each member to take an active role as well as various experiences and efforts to develop the insights, attitudes and skills needed in an effort to prevent problems from arising or in personal development efforts. The aim of the study was to find out the application of group counseling services in improving the emotional control of class XI students at SMA Pakusari Jember. The objects of this study were students of class XI with a total of 6 students who were taken through a purposive sampling technique. The instruments that the researchers used in this study were observation and interviews. The data analysis technique used is data reduction, data presentation and conclusion. From the results of the research that has been done, it can be concluded that group counseling services can improve the emotional control of class XI students at Pakusari State Senior High School in the 2022/2023 Academic Year. Interviews and observations that researchers conducted with students showed an increase in students' emotional control before being given counseling guidance services, namely group guidance services. All students who became the object of research experienced an increase in emotional control from before being given group guidance services Keywords: Group counseling; emotional control Â